Product Perceived Quality and Purchase Intention with Consumer Satisfaction - Muhammad Ibrahim; Asma Saleem; Muhammad Ibrahim (Global Journal of Management and Business Research, 2015)
The purpose of this study is to measure the impact of product perceive quality on purchase intention with level of satisfaction, for meeting this purpose the data was collected by individually through 122 questionnaires by adopting the convenience techniques. Using statistical software hypothesis shows that these variables have positive significant relationship. Practical contribution shows that this study can be used as a guideline to management and marketers to improve the product quality.